The Uzbek model of bioethics: history and modernity - Mukhamedzhanovna, Mukhamedova Zamira; Akmalovna, Umirzakova Nargiza; Nugmanovna, Makhmudova Aziza (Penerbit Universiti Kebangsaan Malaysia, 2020)
Modern biomedical ethics is based on a rich tradition of systematic moral thought, both philosophical and religious. In the XXI century, the interaction and synthesis of natural and humanitarian disciplines are of paramount importance in the system of biomedical education. One of the ways to solve this problem for future specialists is to study the foundations of biomedical ethics, the formation of a bioethical culture of future doctors. Among the ancient scientists of Central Asia who became famous in the field of medicine and pharmacy, a prominent place is occupied by Abuali Ibn Sino (Avicenna), whose life and work can serve as an example of national and historical identity, patriotic education of the youth of Uzbekistan. The emergence of such a phenomenon as the "Muslim Renaissance" and in this context the life and work of Avicenna, his role in the history of the development of medicine in Uzbekistan, are devoted to many, which, like others, were included in the materials of this study. A kind of bridge from ancient medicine to the medicine of the Renaissance and further to modern medicine was the legacy of doctors in Central Asia and Arab physicians. At present, the social, legal and economic aspects of ethical problems of key issues of bioethics in the field of health, medicine and biomedical technologies in the context of the Islamic faith continue to be studied.